Surviving Hitler's war : family life in Germany, 1939 - 48 - Vaizey, Hester 1981- (Genders and sexualities in history, 2010)
Family life under national socialism -- Staying in touch -- Staying in love -- Empowerment or endurance? -- Parents and children